2010
DOI: 10.1111/j.1524-4725.2009.01469.x
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosants

Abstract: Modern sclerosants that have been subjected to rigorous experimental and clinical trials will provide even more efficacious and safer patient treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…52,59 The risk of major complications is difficult to ascertain given a paucity of literature focused directly on STS and polidocanol treatment of VMs, although rare occurrences of anaphylaxis 60 and cardiovascular deterioration 61,62 have occurred with both. However, the majority of complications with both STS and polidocanol are minor, with pain at the injection site and local skin necrosis being the most common 53,63,64 and likely related to tissue extravasation with damage of adjacent vessels at the injection site. 64,65 A recent study has shown greater efficacy with foamed vs liquid injection of polidocanol, 57 and new guidelines suggest both polidocanol and STS should be administered in foam form.…”
Section: Capillary Malformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…52,59 The risk of major complications is difficult to ascertain given a paucity of literature focused directly on STS and polidocanol treatment of VMs, although rare occurrences of anaphylaxis 60 and cardiovascular deterioration 61,62 have occurred with both. However, the majority of complications with both STS and polidocanol are minor, with pain at the injection site and local skin necrosis being the most common 53,63,64 and likely related to tissue extravasation with damage of adjacent vessels at the injection site. 64,65 A recent study has shown greater efficacy with foamed vs liquid injection of polidocanol, 57 and new guidelines suggest both polidocanol and STS should be administered in foam form.…”
Section: Capillary Malformationsmentioning
confidence: 99%
“…Like ethanol, these agents damage vascular endothelial cells causing fibrosis, thrombosis and collapse of the vessel. 52,53 The major benefit of STS and polidocanol is that they are safer than ethanol. However, the improved safety profile of these agents comes at the cost of lower potency than ethanol.…”
Section: Capillary Malformationsmentioning
confidence: 99%
“…In a study of 20 patients with suspected patent foramen ovale or reporting respiratory or cerebral symptoms after foam sclerotherapy, transthoracic echocardiography visualized bubbles in the left heart in 65% of the patients 5 . Moreover, cardiac arrest has been reported after foam sclerotherapy 6 . Skin necrosis has been reported after incorrect application of the sclerosant liquid or foam, and the necessity for amputation after sclerotherapy has been described after incorrect arterial puncture 7 .…”
Section: Discussionmentioning
confidence: 99%
“…It has the advantage over POL (which has anesthetic properties) of not causing cardiovascular effects in very large volumes 2,3 . Disadvantages when compared with POL when higher concentrations are employed include greater risk of extravasation necrosis 4–7 …”
Section: The Studymentioning
confidence: 99%